Two‐Dimensional Conjugated Microporous Polymer with Structural Stability and Electrical Bistability for Rectifying Memory Array. (23rd July 2019) - Liu, Zhengdong; Yin, Yuhang; Wang, Xiangjing; Ju, Shang; Song, Mengya; Zhou, Zhe; Wang, Xiaojing; Cheng, Shuai; Zhang, Zepu; Liu, Juqing; Huang, Wei
Abstract : Rectifying memory is an effective strategy to solve the cross‐talk issues of crossbar switch architecture during the integration procedure for high‐density data storage. Herein, a two‐dimensional (2D) conjugated microporous polymer (CMP) is proposed as an ideal resistive switching medium for integrated rectifying memory devices. Large‐area 2D CMP film is prepared using a surface‐confined polymerization method, featuring rewritable nonvolatile memory with a low set voltage in a graphene/CMP/metal diode. Importantly, this film exhibits outstanding structural stability during solvent immersion and other polymer coating, being suitable for solution‐processed multilayer polymer electronics. By directly stacking the CMP memristor with a poly(3‐hexylthiophene) rectifier, the integrated multilayer device shows desirable rectifying memory effect, effectively reducing the misreading issue induced by the cross‐talk in a crossbar array. Abstract : Large‐area two‐dimensional (2D) conjugated microporous polymers (CMPs) combined merits of structural stability and versatile components are prepared for polymer rewritable nonvolatile memory. Moreover, by directly stacking the CMP memristor with a poly(3‐hexylthiophene) rectifier, the integrated multilayer device shows desirable rectifying memory effect, effectively reducing the misreading issue induced by the cross‐talk in a crossbar array.